Some Characteristics of Cyber Bullying and Cyber Victimization in the Population of Persons With Disabilities: Research Review - Milićević, Milena (Zbornik Instituta za kriminološka i sociološka istraživanja, 2021)
The growing recognition of the dangers associated with cyber victimization and cyberbullying directed against persons with disabilities has led to a noticeable increase in interest in this phenomenon. The paper aims to present the key characteristics of cyberbullying and cyber victimization of persons with disabilities or developmental disabilities, primarily children and adolescents, relying on the findings of the disability studies. First, the conceptual definition of cyber victimization and cyberbullying is presented, along with victimization by traditional bullying. Next, data on the prevalence of these phenomena were presented, as well as their consequences. Different functional and phenomenological characteristics, undesirable outcomes and potential protective and risk factors are addressed. Broadly speaking, the analysis of numerous research on cyber victimization and cyberbullying in this population was conducted to open new research questions and indicate the need to update the study of this problem in our country.